2020
DOI: 10.3389/fmicb.2020.00869
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Relationship of Phyllosphere and Rhizosphere Bacterial Communities During the Development of Bothriochloa ischaemum in Copper Tailings

Abstract: Copper mining and the byproducts associated with the industry have led to serious pollution in the Loess Plateau of China. There is a potential in improving the ecological restoration efficiency of such degraded land through combining microbial and plant remediation approaches. However, the community structure and function of phyllosphere and rhizosphere microorganisms and their response to plant development in copper tailings dams are poorly understood. This study investigated the impact of the phyllosphere a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In particular, it has been proposed that Acidobacteria and Myxoccoccia were able to degrade complex polysaccharides such as cellulose and lignin (Ward et al, 2009;Lambais et al, 2014;Kim et al, 2012), which may explain their higher relative contribution in older leaves in Pinus koraiensis and Picea asperata. Furthermore, a recent study studying leaf position within trees showed that Actinobacteria increased their proportion from the top to the bottom of the canopy (Herrmann et al 2021), and decrease in abundance as the plant grows (Jia et al, 2020), which confirms that Actinobacteria are relatively intolerant to sunny and dry environmental conditions (Shao et al, 2019).…”
Section: Composition Of Phyllosphere Communities Across Different Con...mentioning
confidence: 72%
“…In particular, it has been proposed that Acidobacteria and Myxoccoccia were able to degrade complex polysaccharides such as cellulose and lignin (Ward et al, 2009;Lambais et al, 2014;Kim et al, 2012), which may explain their higher relative contribution in older leaves in Pinus koraiensis and Picea asperata. Furthermore, a recent study studying leaf position within trees showed that Actinobacteria increased their proportion from the top to the bottom of the canopy (Herrmann et al 2021), and decrease in abundance as the plant grows (Jia et al, 2020), which confirms that Actinobacteria are relatively intolerant to sunny and dry environmental conditions (Shao et al, 2019).…”
Section: Composition Of Phyllosphere Communities Across Different Con...mentioning
confidence: 72%
“…In this study, the molecular approach to investigate the bacterial activity at the rhizosphere of P. juliflora revealed that the culturable microbes were higher than those remote of the rhizosphere region, and the root exudates of this plant might influence such activity. The bacterial communities at the rhizosphere are mainly affected by soil environmental factors, such as soil water content, soil nutrients, electrical conductivity, and salinity (Jia et al, 2020), which give rhizosphere microorganisms peculiarities compared to those TABLE 3 | The number of bacterial colonies recorded from soil samples obtained from various locations at the rhizosphere and outer canopy soil of Ghaf (Prosopis cineraria) trees (Al-Thani, 2007).…”
Section: The Microbiology At the Rhizospherementioning
confidence: 99%
“…The rhizosphere and phyllosphere are both affected by different physical and chemical factors, and the nitrogen content of a plant affects the phyllosphere. Other factors related to soil environment and soil solution might have major impacts on the rhizosphere bacterial communities (Jia et al, 2020). Such factors might account for the peculiarities of these bacterial habitats; for example, pigmented bacteria, which are rarely found in the rhizosphere, dominate the leaf surfaces of green plants (Fokkema and Schippers, 1986;Zeng et al, 2014;Jia et al, 2020).…”
Section: Sample Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…The enrichment of microorganisms by the plant is not random, but rather a targeted process [ 22 ]. Several factors (such as geographic regions, soil abiotic factors, and climate conditions) may explain the dramatic variation in the correlation between microbial and plant diversity [ 27 , 28 , 29 , 30 ]. Even within the plant, different plant organs and plant stages are dominated by different microbes [ 31 ].…”
Section: Introductionmentioning
confidence: 99%